(untitled) - Mikhail Heller (New York, 1986)
The book provides an understanding of the cultural and political trends that have made the Soviet Union what it is today. It deals with one particular characteristic - the total influence of the ruling party on all spheres of existence on a scale never before known - acts as a determining force in all Soviet institutions and on the typical Soviet citizen, Homo Sovieticus. The history of the Soviet Union is the history of the transformation of Russia - a country no better or worse than any other, one with its own peculiarities to be sure, but a country comparable in all respects to the other countries of Europe - into a phenomenon such as humanity has never known. On the date of October 25, 1917, under the old Russian calendar (November 7 by the Western calender), a new era began. The history of Russia ended on that day. It was replaced by the history of the Soviet Union. The new era affected the entire human race, because the whole world felt, and still feels, the consequences of the October revolution
Keywords: soviet union - history - 1917-